Soil aquifer treatment to meet reclaimed water requirements. (11th October 2019) - Shabani, Farzaneh; Aflaki, Roshanak; Minamide, Traci; Venezia, Teresa; Stenstrom, Michael K.
Abstract: To increase the opportunities and reduce the cost of indirect potable reuse, soil aquifer treatment (SAT) was evaluated at the City of Los Angeles' Donald C. Tillman Water Reclamation Plant (DCTWRP) in a 2.5‐year pilot study. Six soil columns were operated between February 2016 and November 2018 treating DCTWRP effluent. The goal was to reduce the dissolved organic carbon (DOC) in the effluent to lower concentrations in order to increase the allowable volumes for reclamation. An integrated part of the study was to evaluate the biodegradability of organics in different waters using biodegradable (BDOC) analyses. BDOC has been used in similar research in the past, and in this research, BDOC was an accurate predictor of column performance in removing organic carbon. The total organic carbon in tertiary DCTWRP effluent was reduced from 7 to 10 mg/L to 0.9 to 2.5 mg/L through a process train beginning with ozonation of the tertiary effluent, followed by biological activated carbon, and finally to the soil column effluents. Additional short‐term treatments including reverse osmosis, additional ozonation, and low‐pressure UV were also evaluated. The soil columns removed N‐nitrosodimethylamine to detection limits. Finally, results from SAT and BDOC were used to develop a kinetic model to predict biodegradation of organic matter of wastewater origin through a soil aquifer system. Practitioner points: Soil aquifer treatment is often used in indirect potable reuse projects to protect aquifers. Soil aquifer treatment was simulated in six pilot columns for 2.5 years. Columns were fed tertiary effluent from a nutrient‐removal type‐activated sludge plant. Effluent TOC was reduced from 10 mg/L to 0.9 to 2.5 mg/L, and nitrosodimethylamine (NDMA) was also removed. Biodegradable organic carbon analyses accurately predicted soil column performance in removing organic carbon. Abstract : Treatment processes to simulate Soil Aquifier Treatment.